Production and characterization of Tm3+/Yb3+ codoped waveguides based on PbO-GeO2 thin films - de Assumpção, T. A A; da Silva, D. M.; Del Cacho, V. D.; Kassab, L. R P; Alayo, M. I. (Elsevier, 2013)
Fabrication and optical characterization of Tm3+/Yb3+ codoped PbO-GeO2 (PGO) pedestal-type waveguides are investigated in this work. It is important to mention that, to the best of authors' knowledge, the use of PGO pedestal-type waveguide has not been studied before. PGO thin films codoped with Tm3+ and Yb3+ were obtained through RF magnetron sputtering technique. The pedestal profile was obtained using conventional optical lithography procedures, followed by plasma etching and sputtering deposition. The profile of Tm3+/Yb3+ codoped PGO waveguides was observed by means of Scanning Electron Microscopy (SEM) measurements. Also the infrared and infrared-to-visible frequency upconversion luminescences of Tm3+ ions were measured exciting the samples with a cw 980 nm diode laser. Propagation losses around 11 dB/cm and 9 dB/cm were obtained at 630 and 1050 nm, respectively, for waveguides in the 20-100 μm width range. Single-mode propagation was observed for waveguides width up to 12 μm and 7 μm, at 1050 nm and 630 nm, respectively; larger waveguides width provided multi-mode propagation. The present results corroborate the possibility of using Tm3+/Yb3+ codoped PGO thin films as active waveguide for photonic applications. © 2013 Elsevier B.V. All rights reserved.
Keywords: Germanate; Photonic; Rare-earth ions; Sputtering; Thin film; Waveguide